Correlation of organelle interactions in the development of non-alcoholic fatty liver disease - Liao, Jiabao; Shao, Mengqiu; Zhou, Ze; Wang, Si; Lv, You; Lu, Yanming; Yao, Fang; Li, Wenting; Yang, Ling (Frontiers in Immunology, 2025)
Organelles, despite having distinct functions, interact with each other. Interactions between organelles typically occur at membrane contact sites (MCSs) to maintain cellular homeostasis, allowing the exchange of metabolites and other pieces of information required for normal cellular physiology. Imbalances in organelle interactions may lead to various pathological processes. Increasing evidence suggests that abnormalorganelle interactions contribute to the pathogenesis of non-alcoholic fatty liver disease (NAFLD). However, the key role of organelle interactions in NAFLD has not been fully evaluated and researched. In this review, we summarize the role of organelle interactions in NAFLD and emphasize their correlation with cellular calcium homeostasis, lipid transport, and mitochondrial dynamics.